The Surge of Environmental Social and Governance Reporting and Sustainable Development Goals: Some Normative Thoughts - Chitra S de Silva Lokuwaduge; Ciorstan Smark; Monir Mir (Australasian Accounting, Business and Finance Journal, 2022)
The rising demand for Environmental Social and Governance (ESG) disclosure by stakeholders has created a new tide of sustainability reporting, including Sustainable Development Goals (SDGs). With this new rising tide, the need for enhanced credibility in ESG information has stimulated the development of carbon accounting, ESG disclosure measures and regulations around the world. The aim of this article is to analyse the risks and opportunities of ESG practices and the impact of different stakeholders on the measures, tools and frameworks, including SDGs used among different sectors to report sustainability performance. This study finds that business leaders worldwide have an opportunity to use transparent information about ESG risks and opportunities to promote more effective engagement with investors and other stakeholders and global, national and organisational leaders have a legal and ethical responsibility to deliver sustainable outcomes to their global and local communities.
Keywords: ESG; SDG; sustainability; Carbon accounting; Climate change